MRGPRX2 is negatively targeted by SCF and IL‐4 to diminish pseudo‐allergic stimulation of skin mast cells in culture - Babina, Magda; Wang, Zhao; Artuc, Metin; Guhl, Sven; Zuberbier, Torsten (Experimental dermatology, 2018)
MRGPRX2 was recently uncovered as the “missing link” in clinically relevant mast cell (MC) activation explaining previously puzzling phenomena. It is the receptor for various endogenous ligands and exogenous compounds alike, whose binding evokes rapid degranulation much like allergen‐mediated exocytosis. While the perceivable outcomes are similar, the two activation routes differ regarding mechanism and regulation. We recently reported that acute SCF administration curbs responses evoked by MRGPRX2 in human skin MCs. Maintenance of MCs in culture requires the presence of MC supportive factors and renders the cells functionally and molecularly unequal to ex vivo counterparts. Here, we asked whether expansion in culture impacts the pseudo‐allergic route, and if so, what contribution SCF and IL‐4 play in this scenario. We report that the in vitro micromilieu dampens (but does not erase) pseudo‐allergic responses and that this is accompanied by strongly reduced MRGPRX2 expression. Withdrawal of SCF or IL‐4 individually, but most potently of both collectively, partially reinstates the MRGPRX2 pathway, revealing that SCF and IL‐4 make negative adjustments to the pseudo‐allergic pathway. Under all conditions, the FcεRI‐triggered route showed the inverse pattern of regulation, substantiating that allergic and pseudo‐allergic MC activation can obey opposite rules, hinting at possible competition between them.